Atributos e grupos funcionais de espécies arbóreas em áreas de Floresta Ombrófila Mista no Paraná - Mazon, Joelmir Augustinho (2021)
This survey proposes an ecological grouping of woody species from the Araucaria Mixed Forest (AMF) of Paraná state from a functional approach. For this purpose, functional diversity metrics were calculated for three AMF communities (Floresta Nacional de Irati – FNI, General Carneiro – GNC and São João do Triunfo – SJT) obtained from the values of nine functional traits of the species present in each community, these are: Specific Leaf Area (SLA), Seed Mass (MS), Maximum Potential Height (Hmax), Wood Density (WD), Periodic Annual Increment (PAI), Annual Mortality Rate (M%), Dispersal mode (DM), Reproductive System (RS) and Leaf Renewal (LR). Seventy-eight species were selected from these communities and used as a general sample for the Paraná state AMF, which were grouped using the Hierarchical Cluster method using their trait values. Each group was statistically compared using Generalized Linear Models (GLM) and post hoc tests, interpreted also using Decision Trees (DT) and Canonical Correlation Analysis (CCA). The SJT community had the highest functional diversity, justified by the environmental heterogeneity of its fragments, while FNI had the lowest diversity and functional richness, however, with low divergence in the functional roles of its species, indicating a more stable environmental condition. In other hand, GNC was the community with the greatest richness and functional divergence, denoting that the dominant species in this community plays distinct functional roles. The cluster generated from the 78 species revealed nine groups of ecological strategies, namely: Long-lived pioneers, Wind-dispersed Secondaries, Short-lived pioneers; Pioneers; Facultative secondaries; Small size late trees; Late trees, Secondary Gap Opportunists and Late Secondary. The characteristics of the clusters largely corroborate the theories of ecological resource allocation and compensation strategies, forming ecologically coherent groups that can be extrapolated to the Paraná state AMF.